Thiết kế game AI hỗ trợ dạy học nội dung “Một số yếu tố xác suất” (Toán 5) - Nguyễn Thị Thanh Tuyên, Nguyễn Thị Thanh Tuyên (Tạp chí Giáo dục, 2026)
In the context of the Fourth Industrial Revolution, AI-based games have emerged as a promising research direction in education, particularly in mathematics teaching, due to their potential to provide dynamic interaction, enhance visualization, and support students’ acquisition of knowledge and skills. This study aims to propose an approach to designing and implementing AI-based games for teaching the Grade 5 mathematics topic “selected elements of probability.” The study presents a design procedure and offers an illustrative classroom example of AI-based game integration in probability instruction. The findings provide practical guidance and a useful reference for teachers seeking to incorporate AI-based games into primary mathematics teaching, thereby contributing to improved learning effectiveness in probability at the Grade 5 level.